SOCIAL INTEGRATION OF MULTI-ETHNIC AND RELIGIOUS COMMUNITIES IN THE VILLAGE OF RAMA AGUNG DISTRICT OF ARGAMAKMUR NORTH BENGKULU - Permadi Yahya; Maria Montessori (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
Indonesian society is a pluralistic society, it is characterized by differences in religion, ethnicity, customs, and culture. The diversity of this nation certainly has a value system that is adopted and implemented by the community. Conflicts that occur in a group of people because of the disharmony between communities. Therefore we need social integration that together performs roles following their respective functions. This article aims to analyze the patterns of social integration of multi-ethnic and religious communities in Rama Agung Village, Argamakmur City District, North Bengkulu. This research is qualitative research with case study type, taking the subject using a purposive sampling method. Data analysis techniques used using the Miles and Huberman model, namely data reduction, data display and conclusion drawing, and verification. The findings of this study indicate that the pattern of social integration of multi-ethnic and religious communities in the village of Rama Agung has its uniqueness. Communities unite and form a pattern of reciprocal relations between ethnic and religion based on the values ​​applied in the life of Unity in Diversity. The community upholds a noble culture that continues to be applied and maintained. The values ​​that are built and synergize in society are harmony, unity, justice, kinship, solidarity.